If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(1+6x)=5(2x-1)
We move all terms to the left:
3(1+6x)-(5(2x-1))=0
We add all the numbers together, and all the variables
3(6x+1)-(5(2x-1))=0
We multiply parentheses
18x-(5(2x-1))+3=0
We calculate terms in parentheses: -(5(2x-1)), so:We get rid of parentheses
5(2x-1)
We multiply parentheses
10x-5
Back to the equation:
-(10x-5)
18x-10x+5+3=0
We add all the numbers together, and all the variables
8x+8=0
We move all terms containing x to the left, all other terms to the right
8x=-8
x=-8/8
x=-1
| 145/5=(x+8)/5 | | 4x+1.2=4x+0.2 | | 1x+3x=5 | | 3b+(−12)=−24 | | 1/5(m+2)=3/5-m | | 1/3+x/5=16/3x^2 | | 58/x=2 | | 241=187-y | | 2x+4x=1 | | -10-(-11)=x | | 2x+4x=11x+3x=5 | | y=0.1(1.23)^8 | | 249=29-x | | 3x(x-2)=8x^2-7x | | -4.8(x-3.75)=144.4 | | x+1.62=7.57 | | u-1.79=6.6 | | 1/3+k/5=16/3k^2 | | 13x-3=49 | | y-2.1=7.61 | | y^2+2/3y=0 | | 13=8+5u | | 25=8/3v | | 4•y=96 | | -33=x/5-3 | | 1624=28(p+10) | | 5t+7=T+15 | | 4u+4=32 | | -4x+6X-5=9 | | (8x-1)+27=90 | | 3(y+6)=33 | | 4d-8=8 |